Cancer Genomics : Disease Markers. - Strausberg, R. L. (IOS Press, 2002)
This work states that we are no longer satisfied to study a gene or gene product in isolation, but rather we strive to view each gene within the complex circuitry of a cell. It states that as a family of diseases, all cancer results from changes in the genome.